Schumpeterian growth with technological interdependence: An application to US states - Tim Deeken (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2015)
In this paper, the Schumpeterian growth model developed by Ertur and Koch (2011) that includes spatial interactions between units of observation working via R&D spillovers is presented in detail. The implications of this model and three additional growth models with and without spatial interaction that are nested within this framework are tested for the US states econometrically. It is found that investments in R&D have a positive impact on steady-state income per worker in the Schumpeterian growth model without complex interaction between states, but this effect is absent in the model proposed by Ertur and Koch (2011), even though the estimate for the coefficient measuring interconnectedness between regions is positive and significant. This latter result is robust to alternative specifications of the interaction matrix.
urn:nbn:de:swb:90-504457
Keywords: O18; O47; R11; C31; 330; R&D spillovers; Schumpeterian growth; spatial econometrics